1998
DOI: 10.1021/ma980148r
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Model of Hydrophobically Modified Urethane−Ethoxylate (HEUR) Associative Polymers in Shear Flows

Abstract: This paper describes the rheological behavior of a HEUR (hydrophobic ethoxylated urethane) associative polymer with C16H33 end groups at 2.0 wt % concentration in aqueous solution. Under normal steady shear, this solution exhibits Newtonian behavior at low shear rates and, as the shear rate is increased, passes through a shear-thickening region before exhibiting a sharp decrease in viscosity. Here we report superposition-of-oscillation experiments on steady-shear flows to examine the state of the network struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
324
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 301 publications
(343 citation statements)
references
References 42 publications
18
324
1
Order By: Relevance
“…After a critical stress, the gel structure disrupts and a shear-thinning behaviour is observed. A similar behaviour has been observed by others authors in similar systems [19,29,35]. We have also observed that the zero-shear viscosity always increases with the concentration of polymer and/or non-ionic vesicles in the system.…”
Section: Polymer-vesicle Association Probed By Rheologysupporting
confidence: 91%
“…After a critical stress, the gel structure disrupts and a shear-thinning behaviour is observed. A similar behaviour has been observed by others authors in similar systems [19,29,35]. We have also observed that the zero-shear viscosity always increases with the concentration of polymer and/or non-ionic vesicles in the system.…”
Section: Polymer-vesicle Association Probed By Rheologysupporting
confidence: 91%
“…7,9,38,39 In more viscous physically associating solutions, alternative explanations for strain-stiffening and the related phenomenon of shear thickening have been presented, 8 such as deformation-induced increases in the number of elastically active strands or network components. 40,41 Based on the characterized structure of our triblock copolymer networks 27 and the stress responses observed here, we believe our physically associating networks evolve in the following manner during deformation: as the external shear stress is applied to the network, the distance between the endblock aggregates increases with deformation and the rubbery midblock strands are stretched, adopting non-Gaussian conformations and causing a stiffening of the network. As the midblock is stretched to its maximum extensibility, the stiffening response becomes dominant, causing the stress to rapidly increase.…”
mentioning
confidence: 80%
“…The reversible junctions in transient networks typically contain areas of hydrophobic associations, [7][8][9][10] hydrogen bonding, [11][12][13][14][15][16][17] metal-ligand interactions, 18,19 or ionic associations. 20,21 In many cases such junctions are poorly defined aggregates with unknown association strength and kinetics, but in a few transient network materials bulk properties have been directly correlated to defined polymer microstructure or well-characterized reversible interactions leading to important insights into the properties of these systems.…”
Section: Introductionmentioning
confidence: 99%